Recent advances in the role of rehabilitative therapies for Parkinson’s disease: A literature review - Bazza Sohail; Muhammad Affan Iqbal; Aisha Razzaq; Abdul Wasay Nafe; Robina Malik (Journal of Mind and Medical Sciences)
Regardless of medical therapies and surgical interventions for Parkinson’s disease, patients develop progressive disability. The role of therapies is to maximize functional ability and minimize secondary complications through movement rehabilitation within a context of education and support for the whole person. The overall aim is to optimize independence, safety and wellbeing, thereby enhancing quality of life. Trials have shown that physiotherapy has short-term benefits in Parkinson’s disease. However, which physiotherapy intervention are most effective remains unclear. This article provides a guidance framework rather than a ’recipe’ for treatment. This review shows that a wide range of rehabilitative therapy interventions to treat Parkinson’s disease have been tested. There is a need for more specific trials with improved treatment strategies to underpin the most appropriate choice of therapy intervention and the outcomes measured. According to research in the literature, this review is of particular importance because it discusses many rehabilitation therapies for patients with Parkinson's disease in a single paper, for the first time. The aim of this review article is to evaluate the effectiveness of one therapy intervention compared with a second approach in patients with Parkinson’s disease.